Diminuzioni e accrescimenti Le misure dei maestri di prospettiva - Bartoli, Maria Teresa; Lusoli, Monica (Studi e saggi, 2018)
The perspective in graphic arts was born with a different form than the one used to present it in today's courses, and it developed along with the transformations of scientific thought. This study disassembles from the inside the perspective images of a series of works, and then assembles them again, using clear graphic elaborations to show every step of the process. The sequence of the essays illustrates the evolution of role of the abacus and of measures in the works of the first artist-scientists, according to the scientific thought of the time. From Humanism to Baroque, perspective ceases to be a research on the truth of the eye. On the contrary, it becomes the search of the the eye's deception, exploiting mechanical devices and complex theorems of geometric optics. The original quest is therefore replaced by technical virtuosity. The final repertoire offers a selection of examples showing the wideness of the theme over the centuries.